Implementasi Pola Asuh Positif dan Implikasinya terhadap Perkembangan Sosial Emosional Anak Usia Dini di Lembaga PAUD - Nur Habibah (PEDAGOGIA : JURNAL KEGURUAN DAN PENDIDIKAN, 2025)
Early childhood social-emotional development is a crucial aspect in character building and children's readiness for the next level of education. One of the determining factors in this process is the parenting patterns applied in the early childhood education environment, especially in PAUD institutions. This study aims to examine the implementation of positive parenting by educators and parents and analyse its implications for early childhood social-emotional development in PAUD institutions. This research uses a qualitative approach with an intrinsic case study type. The main source of data came from informants consisting of PAUD teachers, principals, and parents of learners in three purposively selected PAUD institutions. Data collection techniques were conducted through in-depth interviews, participatory observation, and documentation study. Data analysis was conducted using a thematic approach. The results show that the consistent implementation of positive parenting in PAUD institutions contributes significantly to improving children's social-emotional abilities, such as emotion regulation, empathy, and social skills. This success is strongly influenced by teacher competence, parental involvement, and institutional support. On the other hand, institutions that do not have a positive parenting reinforcement system tend to show obstacles in shaping adaptive social behaviour in children. This study recommends the importance of synergy between schools and families in building a positive and sustainable parenting environment.